1997
DOI: 10.1116/1.580560
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-scale lithography on H-passivated Si(100) by atomic force microscope in air

Abstract: We report on the mechanical friction method for a fabrication of a Si nanostructure on a H-passivated Si͑100͒ substrate using an atomic force microscope ͑AFM͒ in a contact mode in air. The bare Si surface region exposed by the mechanical friction between a silicon nitride tip and Si surface was fully oxidized by ambient oxygens. The oxide mask patterns could withstand a selective wet etching process for pattern transfer. The width of the oxide layer formed by an AFM tip was about 200 Å. As the etching time and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 12 publications
(18 reference statements)
0
17
0
Order By: Relevance
“…It was well known that an oxidation layer may be generated on the surface of the scratch area due to the tribochemical reaction. In the previous studies [ 12 - 15 ], such oxidation layer was believed to be the only mask structure on the scratch area. In fact, a thick distorted silicon layer including amorphous and deformed silicon may also be produced under the surface oxidation layer during the scratching process [ 11 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was well known that an oxidation layer may be generated on the surface of the scratch area due to the tribochemical reaction. In the previous studies [ 12 - 15 ], such oxidation layer was believed to be the only mask structure on the scratch area. In fact, a thick distorted silicon layer including amorphous and deformed silicon may also be produced under the surface oxidation layer during the scratching process [ 11 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the mechanical interaction and tribochemical reaction during scratching, the scratched area of the silicon surface may contain a superficial oxidation layer and the tip-disturbed silicon layer in the subsurface [ 11 ]. In the previous studies [ 12 - 15 ], some researchers suggested that the superficial oxygen-rich layer acted as a mask during KOH etching. Little attention has been paid to the tip-disturbed silicon layer in the subsurface [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical friction has also been exploited using AFM in contact mode in air to fabricate silicon nanostructures on a H-passivated Si(100) substrate [34]. An AFM diamond tip sliding on a silicon surface formed protuberances on the substrate under ambient conditions [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…SPM lithography can be used to fabricate nanoscale structures by various methods such as electrochemical oxidation [9][10][11], material transfer [12][13][14], mechanical removal [15][16][17][18][19] and thermal reaction [21,22]. This technique is effective for fabricating nanometer-scale structures.…”
Section: Spm-based Lithographymentioning
confidence: 99%